Dutch-Cantonese Bilinguals Show Segmental Processing during Sinitic Language Production - Timmer, Kalinka; Chen, Yiya (Frontiers in Psychology, 2017)
This study addressed the debate on the primacy of syllable vs. segment (i.e., phoneme) as a functional unit of phonological encoding in syllabic languages by investigating both behavioral and neural responses of Dutch-Cantonese (DC) bilinguals in a color-object picture naming task. Specifically, we investigated whether DC bilinguals exhibit the phonemic processing strategy, evident in monolingual Dutch speakers, during planning of their Cantonese speech production. Participants named the color of colored line-drawings in Cantonese faster when color and object matched in the first segment than when they were mismatched (e.g.,藍駱駝, /laam4/ /lok3to4/, ‘blue camel’; 紅駱駝, /hung4/ /lok3to4/, ‘red camel’). This is in contrast to previous studies in Sinitic languages that did not reveal such phoneme-only facilitation. Phonemic overlap also modulated the event-related potentials (ERPs) in the 125-175, 200-300, and 300-400 ms time windows, suggesting earlier ERP modulations than in previous studies with monolingual Sinitic speakers or unbalanced Sinitic-Germanic bilinguals. Conjointly, our results suggest that, while the syllable may be considered the primary unit of phonological encoding in Sinitic languages, the phoneme can serve as the primary unit of phonological encoding, both behaviorally and neurally, for DC bilinguals. The presence/absence of a segment onset effect in Sinitic languages may be related to the proficiency in the Germanic language of bilinguals.